Predicting the Mental Health of Undergraduate University Students in Northeast India with Academic Psychological Capital: A Cross-sectional and Descriptive Study - Fayaz Ahmad Paul; Indrajeet Banerjee; Arif Ali; Nurnahar Ahmed (Indian Journal of Social Psychiatry)
Background: Undergraduate students are increasingly experiencing and being affected by mental health problems such as depression, anxiety, suicidal thoughts, stress, substance abuse, and self-injury. Transitioning from a high school to a university student is challenging, stressful, and demanding. Objectives: The present study aims to predict the mental health among undergraduate students in Northeast India with academic psychological capital. Materials and Methods: A cross-sectional and descriptive research study was conducted among undergraduate university students. One hundred and twenty students aged between 18 and 25 were recruited for the study through a multi-stage stratified random sampling technique with proportional allocation. The respondents were administered the sociodemographic datasheet, Academic Psychological Capital Questionnaire, and Mental Health Continuum Long Form. Data analysis was done with the help of the Statistical Package of the Social Sciences version 25. Ethical clearance was obtained from the Institutional Ethical Committee. Results: The present study’s findings indicate statistically significant correlations between all of the psychological capital (PsyCap) characteristics and variables related to mental health. Overall-life PsyCap (r = 0.729, P < 0.01), school-work PsyCap (r = 0.610, P < 0.01), and total PsyCap score (r = 0.695, P < 0.01) have a significant positive correlation with total mental health scores. The best model for predicting the mental health score overall-life optimism, overall-life efficacy, and overall-life hope was a linear combination of three of the eight PsyCap variables with R2 = 0.486, F(3,227) = 51.38, P < 0.001. Conclusion: The study shows that PsyCap is associated with the mental health functioning of university students. The findings have important ramifications for the formulation and content of programs designed to support undergraduate students’ mental health and emphasize the value of further study into positive psychological traits as the cornerstones of university students’ positive mental health.